Synthesis of 1,2,4-Dithiazolidines with Arylidene Amino and Arylidene Hydrazino Groups - Choudhari, J.R.; Berad, B.N. (Asian Journal of Chemistry, 2016)
Several 3-phenylimino-4-arylidene amino-5-arylidene hydrazino-1,2,4-dithiazolidines (V) have been synthesized by one step condensation reaction of phenylimino-chloromethane sulphenyl chloride (N-phenyl-S-chloroisothiocarbamoyl chloride) and bis-1,5-arylidene-3-thiocarbohydrazides followed by basification of resultant compounds (IV). The structures of the compounds were established on the basis of elemental analysis, titrimetric analysis and spectral studies.